Preoperative Nodal Biopsy and Extranodal Extension in p16+ Oropharyngeal Squamous Cell Carcinoma - Sindhura Sridhar; Daniel P. Larson; Sweeya Raj; Whitney Jin; Vivian L. Zhu; Melanie Hicks; Kyle Mannion; Michael C. Topf (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Objective ENE is an important prognostic factor in p16‐positive OPSCC and is an indication for adjuvant chemoradiation. A recent single institution retrospective study demonstrated that core needle biopsy (CNB) was independently associated with ENE, potentially due to disruption of the lymph node capsule. In this study, we investigate the association between the type of preoperative nodal biopsy and ENE at our institution. Study Design Retrospective cohort study. Methods Patients with p16‐positive OPSCC who underwent primary surgical resection (transoral robotic surgery and neck dissection) from October 2011 to March 2025 were identified. Univariate logistic regression analysis was performed to determine the association between the type of preoperative biopsy and ENE. The impact of confounding variables was assessed using a multivariate logistic regression model. Results We identified 123 patients with a mean age of 60.9 years (range 38–80). Sixteen patients underwent preoperative CNB (13.0%), 74 patients underwent preoperative FNA (60.2%), and 33 patients did not undergo preoperative biopsy of a lymph node (26.8%). ENE was present in 43 patients (35.0%) including 7/16 (43.8%) CNB, 28/74 (37.8%) FNA, and 8/33 (27.2%) no preoperative biopsy. CNB was not associated with ENE (univariate OR 2.43, 95% CI 0.68–8.84, multivariate OR 2.34, 95% CI 0.50–11.74). Preoperative CNB was not associated with receipt of adjuvant treatment. Patients who presented with more than one clinically positive lymph node (cN2b) had a 48.6% chance of pathological ENE. Conclusion In this single institution study of patients with surgically treated p16‐positive OPSCC, preoperative CNB was not associated with ENE. Level of Evidence: Level 4.